PENDUGAAN PARAMETER MODEL PENINGKATAN POPULASI PEROKOK DENGAN METODE DEKOMPOSISI ADOMIAN MULTISTAGE - Hagni Wijayanti; Fajar Delli Wihartiko (Universitas Pakuan, 2014)
The prevalence of smoking in Indonesia over the years tend to experience increased. Increasing cigarette consumption in Indonesia will affect public health conditions and demanding high fees from the public, so that the necessary control of the consumption of cigarettes wisely. The smoking prevalence of the problem, can be made a mathematical formulation. There are three parameters involved, namely the active smoker population, the population of smokers and potential smokers who've stopped population, along with the change in time. Identify the parameter is very important, because it can show how the problem of the prevalence of smokers. In this study used method of Multistage Adomian Decomposition (MADM) which gives the solution of the model population increase smokers as solution series t (time) for each subinterval m during the period from [0, T]. The resolution of the model and the simulation model do with programming in Mathematica version 8.Key words : method of Multistage Adomian Decomposition (MADM), prevalence of smokers